Genitourinary fistula affixed to uterovaginal prolapse - Rana, A; Amatya, A; Gurung, G; Bista, DK; Joshi, AB; Sayami, K (Journal of Institute of Medicine Nepal, 2007)
Case report: Obstetric genitourinary fistulas 3 [rectovaginal fistula (1), vesicovaginal fistula (2)] all as a consequences of difficult unattended labor in domiciliary settings (eventually with the imminent consecutive vaginal deliveries) congregated by uterovaginal prolapse in two cases giving dual problems of rectovaginal and vesicovaginal fistula with prolapse has been described. A difficult labor in the outset complicated with severe perineal trauma could form a basis for uterovaginal prolapse. Key words: Obstetric genitourinary fistulas, uterovaginal prolapse, perineal trauma The full text of this paper is available at Journal of Institute of Medicine website